DESIGN OF ROBUST H? POWER SYSTEM STABILIZER USING NORMALIZED COPRIME FACTORIZATION - I. Ngamroo; S. Dechanupaprittha (ASEAN Journal on Science and Technology for Development, 2002)
This paper proposes a new design procedure of robust power system stabilizers (PSS) using H? control via normalized coprime factorization (NCF) approach. The design procedure of the proposed PSS is systematically described. Moreover, the selection method of the weighting function in H? control design is explained in a simple manner. The performance and robustness of the proposed PSS are investigated in comparison with the conventional PSS by examining the case of a single machine connected to an infinite bus (SMIB) system. The simulation results are illustrated to ensure the effectiveness of the proposed PSS.